Management of Twak vikruti: a case report - Singh, Swati; Chaudhari, Vaishali R.; Nakade, Mamata (International Journal of Advances in Medicine, 2022)
In today’s era skin disease is very commonly found. As there is no specific and permanent treatment available in modern science therefore people are attracting towards Ayurvedic treatments for skin related issues and diseases. Twak (skin) is the largest organ of human body which protects and covers whole body. It is one of five gyanendriya that is Sparsh gyanendriya (sense organ). Nowadays people use so many chemical products internally as well as externally for looking good which causes the imbalance of dosh, dhatu and mala (fecal product). These are the fundaments of human body and skin is the outer most protective organ. So, whenever anything uncommon happened with body, skin start showing some symptoms like redness, swelling, due to dushti of doshas (imbalance/toxicity of dosha). A male patient of 36 years old came in our hospital with the complains of Twak kandu (skin itching), Krushna varnata (hyper pigmentation), Krushna varni pitikotpatti (rashes), Vali (wrinkles) and Rukshta (dryness) which was diagnosed as Twak vikruti (skin disease) and treated with complete ayurvedic treatment Shaman chikitsa (internal medicine) along with Shodhan chikitsa (body purification treatment).